Effect of patient‐centered self‐management intervention on glycemic control, self‐efficacy, and self‐care behaviors in South Asian adults with type 2 diabetes mellitus: A multicenter randomized controlled trial - Kainat Asmat; Erika Sivarajan Froelicher; Khairunnisa Aziz Dhamani; Raisa Gul; Nazeer Khan (Journal of Diabetes)
Abstract Background This study aimed to test the efficacy of patient‐centered self‐management intervention (PACE‐SMI) to improve HbA1c, self‐efficacy, and self‐care behaviors in adults with type 2 diabetes mellitus (T2DM). Methods In this multicenter, parallel two‐arm randomized controlled trial, 612 adults with T2DM and HbA1c ≥ 7% were enrolled and assigned to the control group (n = 310) and the intervention group (n = 302) using stratified permuted block randomization. The control group received usual care, whereas the intervention group received usual care plus nurse‐led, theory‐driven, culturally tailored PACE‐SMI, comprising eight weekly sessions of individualized education, counseling, behavioral training, and home visit. Outcomes were assessed at baseline, postintervention, and 3 months follow‐up. Results Data at 3 months were provided by 583 participants (control: n = 295, intervention: n = 288). Per‐protocol analysis showed that the intervention group had a lower mean HbA1c (8.49% [standard deviation (SD), 1.58]) than the control group (8.74% [SD, 1.62]), with small yet statistically significant mean difference of 0.25% (95% confidence interval [CI], −0.01 to 0.51; Cohen's d = 0.16; p = 0.03). Self‐efficacy and self‐care behaviors significantly improved in the intervention group (116.89 [SD, 25.50] and 70.01 [SD, 17.97]) compared to the control group (75.43 [SD, 18.99] and 51.54 [SD, 12.04]), with mean differences of 41.48 (95% CI, 37.83–45.13; Cohen's d = 1.84; p < 0.0001) and 18.56 (95% CI, 16.08–21.04; Cohen's d = 1.22; p < 0.0001), respectively. Linear regression analysis indicated the effect of PACE‐SMI on HbA1c was significantly mediated by improvements in self‐efficacy and self‐care behaviors (R2 = 0.232, p < 0.001). Conclusion PACE‐SMI led to modest but significant improvement in HbA1c and substantial enhancements in self‐efficacy and self‐care behaviors in adults with T2DM.